Long non‐coding RNA TINCR suppresses metastatic melanoma dissemination by preventing ATF4 translation. (15th February 2021) - Melixetian, Marine; Bossi, Daniela; Mihailovich, Marija; Punzi, Simona; Barozzi, Iros; Marocchi, Federica; Cuomo, Alessandro; Bonaldi, Tiziana; Testa, Giuseppe; Marine, Jean‐Christophe; Leucci, Eleonora; Minucci, Saverio; et al.
Abstract: Transition from proliferative‐to‐invasive phenotypes promotes metastasis and therapy resistance in melanoma. Reversion of the invasive phenotype, however, is challenged by the poor understanding of mechanisms underlying its maintenance. Here, we report that the lncRNA TINCR is down‐regulated in metastatic melanoma and its silencing increases the expression levels of invasive markers, in vitro migration, in vivo tumor growth, and resistance to BRAF and MEK inhibitors. The critical mediator is ATF4, a central player of the integrated stress response (ISR), which is activated in TINCR‐depleted cells in the absence of starvation and eIF2α phosphorylation. TINCR depletion increases global protein synthesis and induces translational reprogramming, leading to increased translation of mRNAs encoding ATF4 and other ISR proteins. Strikingly, re‐expression of TINCR in metastatic melanoma suppresses the invasive phenotype, reduces numbers of tumor‐initiating cells and metastasis formation, and increases drug sensitivity. Mechanistically, TINCR interacts with mRNAs associated with the invasive phenotype, including ATF4, preventing their binding to ribosomes. Thus, TINCR is a suppressor of the melanoma invasive phenotype, which functions in nutrient‐rich conditions by repressing translation of selected ISR RNAs. SYNOPSIS: Long non‐coding RNA TINCR blocks the acquisition of invasive phenotypes in melanoma, including drug resistance and metastasis dissemination. TINCR targets RNAs associated with invasive phenotypes, preventing their interaction with ribosomes. High TINCR levels prevent translational reprogramming and ATF4 translation, maintaining proliferative, epithelial‐like states. TINCR downregulation leads to translational reprogramming and ATF4 activation, promoting invasion in nutrient‐rich conditions. TINCR interacts with selected integrated stress response RNAs, preventing their binding to the translating ribosomes. Abstract : Long non‐coding RNA TINCR blocks the acquisition of invasive phenotypes in melanoma, including drug resistance and metastasis dissemination. TINCR targets RNAs associated with invasive phenotypes, preventing their interaction with ribosomes.